Comprehensive examination of the athlete`s shoulder - Cotter, E. J.; Hannon, C. P.; Christian, D.; Frank, R. M.; Bach, B. R. (Sports Health: A Multidisciplinary Approach, 2018)
Context: Shoulder pain and dysfunction are common, with patients presenting complaints to both primary and orthopaedic physicians. History and physical examination remain essential to creating a differential diagnosis, even as noninvasive imaging has improved. Evidence Acquisition: Literature was obtained through keyword searches based on the pathology in question (eg, rotator cuff) and the keywords physical examination using PubMed from January 1, 1980, through September 20, 2017. Additional evidence was obtained through screening references from articles identified through the PubMed searches. Study Design: Clinical review. Level of Evidence: Level 3. Results: A total of 7817 articles were screened for relevance. Several physical examination maneuvers have been described for each specific pathology. The Neer sign has a 75% sensitivity for subacromial impingement (SAI), while the Hawkins-Kennedy test has an 80% sensitivity. The painful arc test has an 80% specificity for SAI. The apprehension test has a hazard ratio of 2.96 for anterior shoulder instability. The Jobe test has a sensitivity of 52.6% and a specificity of 82.4% for full-thickness supraspinatus tears, confirmed on arthroscopy. The lag sign is highly sensitive and specific for combined full-thickness supraspinatus and infraspinatus tears at 97% and 93%, respectively. The Speed test has a sensitivity of 54% and specificity of 81% for biceps pathology. The anterior slide test and O`Brien active compression test have been described for superior labrum anterior posterior tears with inconsistent reliability. The cross-body adduction test has a sensitivity of 77% and a specificity of 79% for acromioclavicular joint pathology. Conclusion: Several physical examination maneuvers can isolate specific pathology of the shoulder, with widely ranging sensitivity and specificity.